A atuação do Banco Interamericano de Desenvolvimento no Brasil (1959-2006) - Scherma, Márcio Augusto [UNESP] (2007)
This dissertation examines the lines of action of the Inter-American Development Bank (IADB) in Brazil, since its creation in 1959, until the year 2006 (end of the first government Lula), with the main objective of detecting a possible change in the mode of action of the IADB from the end of the decade of 80 and the early 90, a period of crisis in Latin America. The hypothesis of this dissertation is that although the IADB has been influenced by the prescriptions of the Washington Consensus and some kind of liberal ideas from the United States during the 70¿s-80¿s, the bank¿s roots assured it more independence than others institutions, so that in the case of the IADB, the well-knowned conditionalities in loans were less relevant and contracted with fewer requirements. We believe that the brazilian example is interesting to demonstrate this, because the so-called neoliberal reforms occured later in Brazil than in other Latin American countries; what led us to question what was the real role of international organizations such as the IADB in the process of adopting these reforms. We have chosed the specific case of the IADB because this institution is the largest source of multilateral credit of Brazil